Capsule endoscopy practice during the COVID-19 pandemic: Recommendations from the Capsule Endoscopy Group of the Chinese Society of Digestive Endoscopy - Liao, Zhuan; He, Shuixiang; Sha, Weihong; Feng, Zhijie; Sun, Xiaomei; Wan, Jun; Pan, Jun; Wang, Shasha; Linghu, Enqiang; Li, Zhaoshen; on behalf of the Capsule Endoscopy Group of the Chinese Society of Digestive Endoscopy (Endoscopy International Open, 2021)
The Capsule Endoscopy Group of the Chinese Society of Digestive Endoscopy has issued recommendations for capsule endoscopy (CE) practice during the COVID-19 pandemic to standardize workflow, preventive strategies, and management of a CE unit and in so doing, ensure the safety of both medical staff and patients.